(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2021)
The study aimed to uncover the level of use of modern television technologies and their impact on increasing the watching of news programs on Jordanian television. The study used a descriptive and analytical approach, and the data were collected through developing a scale for the use of modern television technologies for news programs. The sample of the study consisted of (110) workers and technicians in news programs on Jordanian television, chosen by the available deliberate sample method. The results of the study showed that the use of modern television technologies increases the degree of television viewing, especially watching news programs. The study also showed that Jordanian television still uses old television technologies. The study recommended the necessity of transforming Jordanian television into the HD broadcasting technology system instead of the SD system and working on training employees on modern television technologies (infographic, graphics, audio effects, and visual effects).